2000
DOI: 10.1093/clinchem/46.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Antemortem Serum Creatine Kinase, Creatine Kinase-MB, Troponin I, and Troponin T with Cardiac Pathology

Abstract: Background: Spurious increases in serum troponins, especially troponin T, have been reported in patients with and without acute myocardial syndromes. Methods: We studied 78 autopsied patients without clinical myocardial infarction (MI) and correlated histologic cardiac findings with antemortem serum creatine kinase (CK), its MB isoenzyme (CK-MB), cardiac troponin I (cTnI), and cardiac troponin T (cTnT). Results: There was no significant myocardial pathology in 15 patients. Cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(76 citation statements)
references
References 28 publications
4
64
0
3
Order By: Relevance
“…Moreover, we identified a higher sensitivity of cTnI to detect myocardial injury as compared with CK as described by other investigators. 4 Serum cTnI increased earlier after monensin intoxication and an association among cTnI concentration, ventricular dysfunction, and myocardial necrosis was detected, whereas CK was not correlated to any of these measures. This finding is in accordance with previous studies which have shown that CK lacks specificity for myocardial cell injury and that the measurement of CK is not sensitive enough to detect micropathology of the heart in cattle.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, we identified a higher sensitivity of cTnI to detect myocardial injury as compared with CK as described by other investigators. 4 Serum cTnI increased earlier after monensin intoxication and an association among cTnI concentration, ventricular dysfunction, and myocardial necrosis was detected, whereas CK was not correlated to any of these measures. This finding is in accordance with previous studies which have shown that CK lacks specificity for myocardial cell injury and that the measurement of CK is not sensitive enough to detect micropathology of the heart in cattle.…”
Section: Discussionmentioning
confidence: 84%
“…Flunixin-meglumine f (1.1 mg/kg, IV) was given for pyrexia and alleviation of gastrointestinal pain as needed. Blood was collected from the indwelling jugular catheter at 4,6,8,12,16,20,24,36,48,72, and 80 hours (Group A) and at 12, 24, 36, 48, 72, 96, 120, and 144 hours (Group B) after monensin administration for serum biochemical analyses and cTnI measurement. The blood was divided equally and put into tubes without anticoagulant.…”
Section: Methodsmentioning
confidence: 99%
“…Post-mortem evidence suggests the presence of micro-infarction in patients with elevated serum troponins. 81 It is possible that patients with ESRD may sustain repeated subclinical microinfarctions.…”
Section: Aetiology Of An Elevated Cardiac Troponin In Renal Failurementioning
confidence: 99%
“…C ardiac troponin I (cTnI) is a highly sensitive and specific blood marker for the noninvasive diagnosis of increased cardiomyocyte permeability and, as such, has become very important for the early detection of myocardial infarction in human beings. [1][2][3][4][5][6] Although myocardial infarction is uncommon in veterinary medicine, some dogs and cats with conditions involving myocardial damage, such as hypertrophic cardiomyopathy, unclassified cardiomyopathy, dilated cardiomyopathy, subaortic stenosis, mitral valve degeneration, gastric dilatation-volvulus, blunt thoracic trauma, and babesiosis have been found to have high cTnI concentrations. [7][8][9][10][11][12] Cardiac troponin I analyzers have not been standardized and because each company can use a potentially different and proprietary target amino acid in the assay, values obtained on 1 analyzer may not be directly comparable to values obtained on a different analyzer.…”
mentioning
confidence: 99%